Chrysophanol Alleviates Metabolic Syndrome by Activating the SIRT6/AMPK Signaling Pathway in Brown Adipocytes. (16th November 2020) - Liu, Xueying; Yang, Zehong; Li, Huixuan; Luo, Wen; Duan, Wentao; Zhang, Junmei; Zhu, Zhangzhi; Liu, Min; Li, Saimei; Xin, Xiaoyi; Wu, Haoxiang; Xian, Shaoxiang; et al.
Abstract : Chrysophanol, a primary active ingredient of Cassia mimosoides Linn or Rhei radix et rhizoma, has various pharmacological properties, including anticancer, antidiabetic, and anti-inflammatory, as well as blood lipid regulation. However, whether chrysophanol can mitigate obesity, and its underlying mechanisms remains unclear. This study investigated whether chrysophanol effects energy metabolism in high-fat diet- (HFD-) induced obese mice and fat-specific Sirtuin 6- (SIRT6-) knockout (FKO) mice, targeting the SIRT6/AMPK signaling pathway in brown and white fat tissue. Our results showed that chrysophanol can effectively inhibit lipid accumulation in vitro and reduce mice's body weight, improve insulin sensitivity and reduced fat content of mice, and induce energy consumption in HFD- induced obese mice by activating the SIRT6/AMPK pathway. However, a treatment with OSS-128167, an SIRT6 inhibitor, or si-SIRT6, SIRT6 target specific small interfering RNA, in vitro blocked chrysophanol inhibition of lipid accumulation. Similar results were obtained when blocking the AMPK pathway. Moreover, in the HFD- induced obese model with SIRT6 FKO mice, histological analysis and genetic test results showed that chrysophanol treatment did not reduce lipid droplets and upregulated the uncoupling protein 1 (UCP1) expression. Rather, it upregulated the expression of thermogenic genes and activated white fat breakdown by inducing phosphorylation of adenosine 5 ′ - monophosphate- (AMP-) activated protein kinase (AMPK), both in vitro and in vivo. OSS-128167 or si-SIRT6 blocked chrysophanol's upregulation of peroxisome proliferator-activated receptor- γ coactivator-1 α (Pgc-1 α ) and Ucp1 expression. In conclusion, this study demonstrated that chrysophanol can activate brown fat through the SIRT6/AMPK pathway and increase energy consumption, insulin sensitivity, and heat production, thereby alleviating obesity and metabolic disorders.